A conceptual assessment model to identify phase of industrial cluster life cycle in Indonesia - Naniek Utami Handayani; Andi Cakravastia; Lucia Diawati; Senator Nur Bahagia (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: The purpose of this research is to develop an assessment model to identify phase of industrial cluster life cycle which comprises definition of the cycle phases, identification of assessment components, and characterization of each phase of cluster life cycle.Design/methodology/approach: This research uses the Delphi method to develop the conceptual model i.e. define phases of cluster life cycle and identify assessment components, and design typology of cluster life cycle. Findings: The proposed indicators used to assess industrial cluster phases are (i) concentration of industry, (ii) market accessibility, (iii) completeness of actors, and (iv) collaboration of stakeholders. Research limitations/implications: This study developed a conceptual model based on expert opinion in Indonesia. Given the limitations of experts in this field in Indonesia, it is necessary to develop advanced research involving more experts and if possible, to involve experts outside Indonesia. Practical implications: This paper provides an assessment conceptual model to identify phase of industrial cluster life cycle. The objective of assessing industrial cluster phases is to evaluate and improve the condition of industrial clusters and as basis for formulation policy interventions in accordance with each phase of cluster life cycle. The final results of this study are the position of each cluster on their life cycle, which reflects the condition of each industrial cluster. On a practical level, the assessment result could be used to improve the competitiveness of industrial sectors and help local and central government to formulate appropriate policy interventions. Originality/value: The paper provides an assessment conceptual model to identify phases of industrial cluster life cycle, which include definition phases, assessment components and typology of each phase of cluster life cycle based on assessment criteria. Research in this field was rarely done by the other researchers.
Keywords: 650; assessment conceptual model; identify phase; industrial cluster; life cycle; policy interventions